Performance Measurement of Comprehensive Emergency Neonatal Obstetric Servant (PONEK) in Dr. Mohammad Hoesin General Hospital Palembang with a Balanced Scorecard to Improve the Quality of Midwifery Services - Sastradinata, Irawan (HM Publisher, 2021)
Introduction: Maternal Mortality Rate (MMR) and Neonatal Mortality Rate (IMR) in Indonesia are the highest among ASEAN countries, namely 307 / 100.000 live births for MMR and 20/1000 live births for IMR. This situation can actually be prevented through early detection approaches and appropriate management of mothers and babies through the Comprehensive Obstetric Neonatal Emergency Services (PONEK) program as one of the important elements of good hospital service performance. The performance of a hospital is of course determined by the performance of each unit and team which requires relevant multi-dimensional measurement standards. Basic Score Card (BSC) is a method developed by Kaplan and Norton (1996) to measure performance comprehensively, so it is hoped that this method can help improve the quality of obstetric emergency services, especially in Palembang. Methods: This descriptive analytic study was conducted at Dr. Mohammad Hoesin (RSMH) Palembang by looking for factors that affect the quality of emergency obstetric care and analyzing the performance of the PONEK team in providing PONEK services. Primary data is obtained through questionnaires with direct interviews with respondents or by direct observation in the field to see the real obstacles that occur during service. The data were analyzed qualitatively and quantitatively. Results: During the period October 2014 - March 2015 there were 1219 total hospitalized patients. Based on the Financial Perspective, the effectiveness ratio for achieving the performance of the RSMH PONEK team still meets the target of 1.3 for vaginal and has not met the target of 0.5 for SC with a financial perspective score of +2. Based on the Customer Perspective, the total score is +2 with the patient satisfaction index is 5957 (satisfied) and the Gross Death Rate (GDR) figure for PONEK RSMH services is 14 (meets GDS MOH standards). Based on the Internal Business Perspective the total score is +1, with the level of compliance with the clinical pathway standard = 92%, the level of compliance for the National Fornas PONEK = 100%, while the response time is > 1 hour. Based on the perspective of learning and growth, the total score = +1, with the number of PONEK trained personnel <50%, neonatal resuscitation and lactation management <10%, employee work motivation is very high, and facilities and infrastructure are classified as good. Based on these four perspectives, the BSC score for RSMH PONEK performance is +0.6 with an interval scale of -1 to +1. Conclusion: Based on the BSC measurement results of the PONEK team at RSMH Palembang, it can be concluded that the PONEK team's performance is good.